Successful Treatment of Dandy-Walker Syndrome by Endoscopic Third Ventriculostomy in a 6-Month-Old Girl With Progressive Hydrocephalus: A Case Report and Literature Review - Chih-Fen Hu; Hueng-Chuen Fan; Cheng-Fu Chang; Chih-Chien Wang; Shyi-Jou Chen (Elsevier, 2011)
Dandy-Walker syndrome (DWS) is a congenital brain malformation involving the cerebellum and fourth ventricle. We report a 6-month-old girl with DWS presenting an initially normal ventricular system and mild cyst-like lesion over the posterior fossa as assessed by postnatal brain sonography. However, symptoms and signs of increased intracranial cerebral pressure in terms of frequent vomiting and tense anterior fontanel developed, and these were associated with mild hypotonia and poor neck support, and upward-gaze palsy at the age of 6 months. Magnetic resonance imaging revealed a huge cystic lesion of the fourth ventricle, which filled the posterior fossa and ventricular dilatation. The tentorium was progressively displaced upward by the cyst. A nearly complete agenesis of the cerebellar vermis was also confirmed. After a successful endoscopic third ventriculostomy, a series of brain magnetic resonance imaging scans, taken during a follow-up survey, showed normal lateral and third ventricles. Consequently, symptoms of intracranial cerebral pressure resolved, and a developmental milestone was achieved. In conclusion, DWS can be confirmed postpartum, and endoscopic third ventriculostomy was found to be a preferential operative procedure for DWS with hydrocephalus. It may be effective for patients younger than 1 year.